The paradox of civic education in Malawi's education system: regaining the missed opportunities - Chibambo, Mackenzie Ishmael; Divala, Joseph Jinja (Frontiers in Political Science, 2023)
There is a common assumption that the removal of civics from the curriculum between 1995 and 2002, when Malawi became a democracy might have deformed citizenship and civic education (CE). This narrative assumes that civics, as a discipline, was critical for instilling democratic and civic values among Malawians. This then prompted the Tonse Alliance Government (TAG) to change the Ministry of Civic Education and Culture (MoCC) to the Ministry of Civic Education and National Unity (MoCENU) as the first step. Additionally, the then Minister of MoCENU proposed a policy change to reintroduce civics in schools arguing that, it is only through this subject that democratic citizenship can be realized. Accordingly, this paper sought to argue that mere changing of MoCC to MoCENU, and reintroducing civics in schools may add nothing towards the creation of democratic citizenship when we consider global trends. This paper therefore utilized qualitative research design especially Critical Hermeneutics to analyze available literature on citizenship and CE trends, its conceptions, and common issues around the globe. In doing so, the paper sought to explain whether Malawi’s CE projects have been on the right trajectory or not, and how power relations and political interests have shaped its development. Mainly, we ascribed to the epigram that, straightening a tree is better done in its sapling. In other words, the best spaces for behavior change and habit formation remain the schools because they are naturally designed to prepare children for such roles and functions. While our arguments might not be final, we still understand that many researchers have held a fragmented view of citizenship and CE. We thus sought to analyze these two concepts in the lenses of Critical Pedagogy as suggested by Paulo Freire and Henry Giroux who understood schools as political spaces where the hegemony captures the curriculum to oppress society while protecting their interests. By advocating for a democratic model of education anchored in humanization, problem-posing, and critical conscientization, Critical Pedagogy molds students into future citizens who value critical thinking, transparency, and democratic values.